ISLAMIC ECONOMIC LAW ON MUSYARAKAH AND MURABAHAH: IMPACTS ON ISLAMIC BANKING GROWTH - Pramita, Adinda Dian; Fikriyah, Khusnul; Suryaningsih, Sri Abidah (Universitas Islam Negeri Mataram, 2024)
This research uses a qualitative approach with a literature study method to explore the performance of Islamic banking. This method allows researchers to understand the natural context of the phenomenon under study through data collection from various relevant literature, such as official reports from Bank Indonesia, the Financial Services Authority, and Islamic economic literature. This qualitative analysis aims to describe the condition and performance of Islamic banking in detail and in depth. The results show that Islamic banking has experienced significant growth in several indicators, such as asset growth and financing, compared to conventional banking. However, financing is still dominated by the consumptive sector, with MSME financing remaining low. The study also highlights the differences between murabaha and musyarakah contracts, as well as Islamic banking faces challenges such as limited product offerings and financial literacy issues. The key differences between Murabahah, a cost-plus sale contract, and Musyarakah, a partnership contract based on profit and loss sharing, lie in the way risks and profits are distributed.